The linguistic and stylistic content in teaching Spanish in Gabon: attitudes and teaching practices - Jeanne Berthe MAKAYA MAVOUNGOU (Ediciones Universidad de Salamanca, 2016)
Always it has made us perplex, the position thought by the majority of the professorship gabonés as for if we have to or not to be interested to the partial or complete study of the linguistic and semantic aspects during the explanation and comment of a document. The education of the language and of the Spanish literature needs of the teacher the capture in account and the knowledge of the synergy that exists between the different genres, the aesthetic expression, the semantic content and the pragmatic use. It is the reason by which there is expected from the teacher, the capture in account of the contributions of other such connected sciences as the linguistics, the aesthetics, the sociology, the psychology, etc. That do not stop suggesting to the pedagogy and to the didactics other tracks of treatment of the suitable contents in class of Spanish language. The contribution of this investigation places, especially, to level of the analysis of the educational practices and the contributions of these by means of the semantic and linguistic paths.